Gaya Hidup Siswa Lebih Menentukan Kemampuan Pengelolaan Keuangan Syariah Dibandingkan dengan Literasi Keuangan Syariah - Anita, Anita; Khusaini, Khusaini; Lestari, Sri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One indicator of sharia financial management is funding made by students. However, not all students manage their finances well. This study aims to examine the effect of Islamic financial literacy and lifestyle variables on students' Islamic financial management. The authors utilized a cross-sectional survey. The sample size used was 104 students of class X Madrasah Aliyah Negeri 2 Tangerang Regency and census as the sampling technique. As for determining the size of the questionnaire using google form through the student's WhatsApp group and having tested its validity and reliability. The author utilized a logistic regression model for testing. The results showed that sharia financial literacy was a significant determinant in improving Islamic financial management. In other words, the higher the student's financial literacy, the better the possibility to manage finances in a sharia manner for students. This showed that the higher student knowledge about finance, managerial ability in sharia would increase. Likewise, students' lifestyles were also a significant determinant in improving students' sharia financial management. The lifestyle in question was that students carry out positive activities, had high interest in learning, had a positive opinions, allocated money appropriately, and utilized money according to their needs. Student lifestyle had a higher influence than financial literacy in determining sharia financial management. The findings of this study provide scientific contributions, especially in the field of education and help students to have good attitudes and behavior in managing finances inside and outside school.